2008
DOI: 10.1128/jvi.02752-07
|View full text |Cite
|
Sign up to set email alerts
|

Murine Gammaherpesvirus 68 Open Reading Frame 75c Tegument Protein Induces the Degradation of PML and Is Essential for Production of Infectious Virus

Abstract: Promyelocytic Leukemia nuclear body (PML NB) proteins mediate an intrinsic cellular host defense response against virus infections. Herpesviruses express proteins that modulate PML or PML-associated proteins by a variety of strategies, including degradation of PML or relocalization of PML NB proteins. The consequences of PML-herpesvirus interactions during infection in vivo have yet to be investigated in detail, largely because of the species-specific tropism of many human herpesviruses. Murine gammaherpesviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 70 publications
3
82
2
Order By: Relevance
“…There is increasing evidence that several ND10 components contribute to intrinsic cellular resistance to a variety of herpesvirus infections (Cantrell and Bresnahan, 2006;Everett et al, 2008a;Kyratsous and Silverstein, 2009;Ling et al, 2008;Lukashchuk et al, 2008;Lukashchuk et al, 2010;Negorev et al, 2006;Preston and Nicholl, 2006;Saffert and Kalejta, 2006;Tavalai et al, 2006;Tavalai et al, 2008;Woodhall et al, 2006). We have shown that depletion of PML increases the replication efficiency of ICP0-null mutant HSV-1 (Everett et al, 2008a;Everett et al, 2006;Everett et al, 2008b), a finding that implicates PML in a repression mechanism that targets HSV-1 genomes and which is inactivated by ICP0 during the course of a wild-type virus infection.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…There is increasing evidence that several ND10 components contribute to intrinsic cellular resistance to a variety of herpesvirus infections (Cantrell and Bresnahan, 2006;Everett et al, 2008a;Kyratsous and Silverstein, 2009;Ling et al, 2008;Lukashchuk et al, 2008;Lukashchuk et al, 2010;Negorev et al, 2006;Preston and Nicholl, 2006;Saffert and Kalejta, 2006;Tavalai et al, 2006;Tavalai et al, 2008;Woodhall et al, 2006). We have shown that depletion of PML increases the replication efficiency of ICP0-null mutant HSV-1 (Everett et al, 2008a;Everett et al, 2006;Everett et al, 2008b), a finding that implicates PML in a repression mechanism that targets HSV-1 genomes and which is inactivated by ICP0 during the course of a wild-type virus infection.…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, PML.I is able partially to reverse the effect of PML depletion on ICP0-null mutant plaque formation and is naturally the most highly expressed in human cells (Condemine et al, 2006). Recently, PML.I expression in PML-negative mouse fibroblasts was found to decrease the robust replication of murine -herpesvirus 68 normally observed in these cells in comparison to control PML-positive fibroblasts (Ling et al, 2008). Given that PML.II also had a repressive effect in our assays, it is of interest that this isoform interacts specifically with adenovirus E4orf3 protein, thereby enabling the mechanism by which E4orf3 disrupts ND10 during adenovirus infection (Hoppe et al, 2006;Leppard et al, 2009).…”
mentioning
confidence: 99%
“…Primary antibodies used in this study include goat polyclonal anti-GFP (1:2,000 dilution; Rockland Immunochemicals, Inc., 600-101-215), mouse monoclonal anti-FLAG (1:1,000 dilution; Sigma-Aldrich, F3165), horseradish peroxidase (HRP)-conjugated rabbit anti-FLAG (1:2,000 dilution; Sigma-Aldrich, A8592), rabbit monoclonal anti-Hsc70 (1:2,000 dilution; Cell Signaling Technology, D12F2), rabbit monoclonal anti-histone H3 (1:2,000 dilution; Cell Signaling Technology, 9715), rabbit polyclonal mLANA antiserum (1:2,000 dilution) (15), mouse polyclonal MHV68 antiserum (1:1,000 dilution) (46), rabbit monoclonal anti-GAPDH (antiglyceraldehyde-3-phosphate dehydrogenase) (1:1,000 dilution; Cell Signaling Technology, 2118), rabbit polyclonal ORF57 antiserum (1:2,000 dilution) (47), chicken anti-ORF59 IgY (1:250 dilution) (46), mouse monoclonal anti-␤-actin (1:5,000 dilution; Sigma-Aldrich, A2228), and mouse monoclonal anti-GST-HRP (1:1,000 dilution; Santa Cruz Biotechnology, sc-138). Fluorophore-conjugated secondary antibodies used in this study include Alexa Fluor donkey anti-goat 488, Alexa Fluor goat anti-mouse 568, and Alexa Fluor goat anti-chicken 568 (Life Technologies).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…ORF75c induces proteasomal degradation of PML complexes leading to a dispersal of ND10 components and a reduction in SUMOylation, Daxx and Sp100 levels (108,180). Researchers found that…”
Section: Mhv-68 Orf75mentioning
confidence: 99%
“…The majority of functional data regarding the herpesvirus tegument comes primarily from research on alpha and betaherpesviruses, which has shown that tegument proteins function in crucial roles in viral replication, including transcytosis of the herpesvirus capsid toward the nucleus during initial infection and egress from the nucleus toward the periphery during lytic replication (27,113,187,295,350). Additional functions of tegument proteins include modulation of the host cell environment during the immediate-early phase of infection (294), including shut off of host gene expression (289,301,302), antagonism of innate antiviral host response (102,147,178,180,276,362), and assembly and egress of herpesvirus virions ( (27,57,120,277) and reviewed in (213)). …”
Section: Introductionmentioning
confidence: 99%